The General Traveling Wave Solutions of the Fisher Equation with Degree Three. (22nd September 2013) - Yuan, Wenjun; Chen, Qiuhui; Qi, Jianming; Li, Yezhou
Abstract : We employ the complex method to research the integrality of the Fisher equations with degree three. We obtain the sufficient and necessary condition of the integrable of the Fisher equations with degree three and the general meromorphic solutions of the integrable Fisher equations with degree three, which improves the corresponding results obtained by Feng and Li (2006), Guo and Chen (1991), and Ağırseven and Öziş (2010). Moreover, allw g, 1 ( z ) are new general meromorphic solutions of the Fisher equations with degree three forc = ± 3 / 2 . Our results show that the complex method provides a powerful mathematical tool for solving a large number of nonlinear partial differential equations in mathematical physics.